2019
DOI: 10.1111/1462-2920.14832
|View full text |Cite
|
Sign up to set email alerts
|

A crosstalk between c‐di‐GMP and cAMP in regulating transcription of GcsA, a diguanylate cyclase involved in swimming motility in Pseudomonas putida

Abstract: SummaryThe ubiquitous bacterial second messenger c‐di‐GMP is synthesized by diguanylate cyclase (DGC) and degraded by phosphodiesterase (PDE). Pseudomonas putida has dozens of DGC/PDE‐encoding genes in its genome, but the phenotypical–genotypical correlation and transcriptional regulation of these genes are largely unknown. Herein, we characterize function and transcriptional regulation of a P. putida c‐di‐GMP‐metabolizing enzyme, GcsA. GcsA consists of two per‐ARNT‐sim (PAS) domains, followed by a canonical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Our investigation of another target gene, cyaA , reveals the role of c-di-GMP/FleQ in cAMP synthesis regulation, which is in line with the previous findings that high-level c-di-GMP decreased cAMP content in P. aeruginosa and P. putida ( 28 , 29 ). However, the mechanism behind this negative correlation between the 2 second messengers remains unknown.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our investigation of another target gene, cyaA , reveals the role of c-di-GMP/FleQ in cAMP synthesis regulation, which is in line with the previous findings that high-level c-di-GMP decreased cAMP content in P. aeruginosa and P. putida ( 28 , 29 ). However, the mechanism behind this negative correlation between the 2 second messengers remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…cyaA , encoding an adenylate cyclase, is responsible for synthesis of another second messenger, cAMP, in P. putida ( 27 ). Both a previous study in P. aeruginosa and our recent study in P. putida revealed that high-level c-di-GMP can decrease the content of cAMP, but their correlation mechanism remains unclear ( 28 , 29 ). In this study, our result showed that c-di-GMP regulated the expression of cyaA in an FleQ-dependent manner.…”
Section: Resultsmentioning
confidence: 87%
“…c‐di‐GMP was extracted and quantitated as described previously (Xiao et al ., 2020). Overnight grown P .…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Xiao et al . (2020) showed that Crp P . putida directly represses the expression of gcs A (a novel diguanylate cyclase involved in the repression of swimming motility) in a cAMP‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%